Legal Politics of the Religious Court in Indonesia and the Turkish Legal System - Siti Kasiyati; Abdullah Tri Wahyudi; Muhammad Julijanto; Muhammad Taufiq (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyse the development and compare the legal politics of the Religious Court in Indonesia and Turkey. This study is library research with an interdisciplinary approach to historical-legal and comparative law research. This study presents a historical-legal perspective and a comparative analysis of the law to obtain similarities and differences in the legal politics of the Religious Court in Indonesia and Turkey. The legal politics of the Religious Court in Indonesia are divided into pre-Colonial, independence, and reform periods. In Turkey, the Religious Court is divided into three periods: before the Tanzimat, after the Tanzimat, and during Mustafa Kemal Atatürk's reforms. A comparative analysis of the law found that the Religious Courts in Indonesia and Turkey initially applied Islamic law. Still, later restrictions were placed on it in an attempt to abolish it. The difference is that the Religious Court in Indonesia still enforces Islamic law as a positive law in certain fields and regions. The Religious Court in Turkey was abolished and replaced by a regular Court based on European law. The existence of the Religious Court in Indonesia demonstrates the success of legal pluralism, while legal secularism has shifted legal pluralism in Turkey.